PsycEXTRA Dataset 2004
DOI: 10.1037/e425272005-001
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Validating a Model of Interpersonal Performance Dimensions

Abstract: fiSSTRACT (Maximum 200 vmrds):Current models of job performance recognize its multidimensional nature but do not provide a comprehensive picture of the interpersonal requirements of jobs. As a first step toward developing a more cogent and comprehensive understanding of interpersonal performance, a taxonomy of the interpersonal requirements of jobs was developed and validated. An extensive literature review of interpersonal performance behaviors was conducted to develop a proposed taxonomy of interpersonal per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Gayvert (1999, p. 21) supports such a depiction when he argues that Army leadership 'ought to be identified, taught and discussed as a function, or set of functions, different from management, administration or command." Describing the leadership domain in detail is an extension of the work of Campbell et al (1993), Borman et al (1987), and Hedge et al (2004) and comparable to the work of Carpenter and Wisecarver (2004) in their recent identification of interpersonal performance dimensions. The depiction of Army leadership under examination in this study is one means for synthesizing the results of significant leadership research findings into a single model which better expresses the roles, processes, and goals of leadership within the Army.…”
Section: Why Describe Leadership In Terms Of Competencies?mentioning
confidence: 99%
“…Gayvert (1999, p. 21) supports such a depiction when he argues that Army leadership 'ought to be identified, taught and discussed as a function, or set of functions, different from management, administration or command." Describing the leadership domain in detail is an extension of the work of Campbell et al (1993), Borman et al (1987), and Hedge et al (2004) and comparable to the work of Carpenter and Wisecarver (2004) in their recent identification of interpersonal performance dimensions. The depiction of Army leadership under examination in this study is one means for synthesizing the results of significant leadership research findings into a single model which better expresses the roles, processes, and goals of leadership within the Army.…”
Section: Why Describe Leadership In Terms Of Competencies?mentioning
confidence: 99%
“…In another investigation of the interpersonal performance dimensions of military leaders, Carpenter and Wisecarver (2004) collected 1186 critical incidents from 175 Soldiers and found that Soldiers from all Military Occupation Skills (MOS) and ranks believed that interpersonal skills are important. Carpenter and Wisecarver then constructed and validated an interpersonal performance taxonomy that indicated the primary dimensions of interpersonal performance were:…”
Section: The Interpersonal Skills Of Leadershipmentioning
confidence: 99%
“…(1) Rewarding others Both the work of Sternberg et al (2000) and Carpenter and Wisecarver (2004) overlap with many of the leadership competencies recently outlined in Army leader doctrine. This overlap is noted in Table I and provides a basis for a leader development program or curriculum in the area of interpersonal skills.…”
Section: The Interpersonal Skills Of Leadershipmentioning
confidence: 99%
“…An interpersonal performance model with four general dimensions and 16 sub-dimensions was developed through research at the U.S. Army Research Institute for the Behavioral and Social Sciences (ARI) (Carpenter & Wisecarver, 2004). Support for the model was gathered from a critical incident sort of over 1,000 critical incidents and from survey data collected from individuals representing 81 different jobs.…”
Section: Interpersonal Performance Modelmentioning
confidence: 99%
“…There are a number of aspects of the Special Forces job that require interpersonally-based skills, including the need for teamwork, diplomacy, and skill in training others (e.g., see Carpenter and Wisecarver, 2004).…”
Section: Need For Interpersonal Skill In Special Forcesmentioning
confidence: 99%